Microenvironmental regulation of T-cells in pulmonary hypertension - Plecitá-Hlavatá, Lydie; Brázdová, Andrea; Křivonosková, Monika; Hu, Cheng-Jun; Phang, Tzu; Tauber, Jan; Li, Min; Zhang, Hui; Hoetzenecker, Konrad; Crnkovic, Slaven; Kwapiszewska, Grazyna; Stenmark, Kurt R. (Frontiers in Immunology, 2023)
Introduction In pulmonary hypertension (PH), pulmonary arterial remodeling is often accompanied by perivascular inflammation. The inflammation is characterized by the accumulation of activated macrophages and lymphocytes within the adventitial stroma, which is comprised primarily of fibroblasts. The well-known ability of fibroblasts to secrete interleukins and chemokines has previously been implicated as contributing to this tissue-specific inflammation in PH vessels. We were interested if pulmonary fibroblasts from PH arteries contribute to microenvironmental changes that could activate and polarize T-cells in PH. Methods We used single-cell RNA sequencing of intact bovine distal pulmonary arteries (dPAs) from PH and control animals and flow cytometry, mRNA expression analysis, and respirometry analysis of blood-derived bovine/human T-cells exposed to conditioned media obtained from pulmonary fibroblasts of PH/control animals and IPAH/control patients (CM-(h)PH Fibs vs CM-(h)CO Fibs). Results Single-cell RNA sequencing of intact bovine dPAs from PH and control animals revealed a pro-inflammatory phenotype of CD4+ T-cells and simultaneous absence of regulatory T-cells (FoxP3+ Tregs). By exposing T-cells to CM-(h)PH Fibs we stimulated their proinflammatory differentiation documented by increased IFNγ and decreased IL4, IL10, and TGFβ mRNA and protein expression. Interestingly, we demonstrated a reduction in the number of suppressive T-cell subsets, i.e., human/bovine Tregs and bovine γδ T-cells treated with CM-(h)PH-Fibs. We also noted inhibition of anti-inflammatory cytokine expression (IL10, TGFβ, IL4). Pro-inflammatory polarization of bovine T-cells exposed to CM-PH Fibs correlated with metabolic shift to glycolysis and lactate production with increased prooxidant intracellular status as well as increased proliferation of T-cells. To determine whether metabolic reprogramming of PH-Fibs was directly contributing to the effects of PH-Fibs conditioned media on T-cell polarization, we treated PH-Fibs with the HDAC inhibitor SAHA, which was previously shown to normalize metabolic status and examined the effects of the conditioned media. We observed significant suppression of inflammatory polarization associated with decreased T-cell proliferation and recovery of mitochondrial energy metabolism. Conclusion This study demonstrates how the pulmonary fibroblast-derived microenvironment can activate and differentiate T-cells to trigger local inflammation, which is part of the vascular wall remodeling process in PH.